TRAINING FOR THE UNIVERSAL MUSEUM (Cadernos de Sociomuseologia, 2009)
"TRAINING FOR THE UNIVERSAL MUSEUM" addresses a theme of our time. A Canadian, Marshall McLuhan, coined the phrase "global village" for this age which has witnessed mass travel, mass communications, even mass credit. Are we now about to see the "mass museum", a museum presumably homogenized and popularized for whatever constitutes the greatest cohort of global visitor which might arrive on the doorsteps of every-museum, every-where? The contributors to this volume think not. But there is in these papers some evidence of worry that we as individuals and institutions responsible for the education and professional development of museum workers are failing to consider seriously the impacts of the "global" forces at work in modern societies. Angelica Ruge discusses how the Germans are re-organizing museum training into a cohesive scheme, searching out the best elements from the former two states that now comprise the new German state. Margaret Greeves and Chris Newbery document the British search for a value free (and universally applicable?) set of museological skills which will underpin performance standards in the workplace. Both of these papers offer a response to the redefinition of the post-modern national state which as we watch, is redrawing political boundaries on every continent, and emphasizing the portability of skills and learning for the itinerant knowledge-industry worker.